Answer:
Option C is correct.
Step-by-step explanation:
The exponential function is of the form: ![f(x) = ab^x](https://tex.z-dn.net/?f=f%28x%29%20%3D%20ab%5Ex)
where a is initial value and b is the base.
*If base b>1
(i) For positive value of a.
If x increases then, f(x) tends to positive infinity.
(ii)For negative value of a.
if x increases, then f(x) tends to negative infinity.
*if 0<b<1 ,
(i)For positive value of a.
If x increases then, f(x) tends to 0.
(ii)For negative value of a.
if x increases, then f(x) tends to 0.
Given the exponential function ![f(x) = -4(2)^x](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-4%282%29%5Ex)
Here, value of a = -4 and b = 2>1
From the above definition,
as we increase x
, f(x)
.
Y-intercept ( plug x =0 to solve for y)
Substitute the value of x =0 in given equation;
![y =-4(2)^0 = -4 \cdot 1 = -4](https://tex.z-dn.net/?f=y%20%3D-4%282%29%5E0%20%3D%20-4%20%5Ccdot%201%20%3D%20-4)
Y-intercept (0, -4)
Therefore, the only correct option is C because if we increase the value of x, the function f(x) tends to negative infinity and also it cut the y-axis at y = -4.